All-acoustic signal modulation and logic operation via defect induced cavity effects in phononic crystal coupled-resonator acoustic waveguides. (6th November 2019) - Reyes, Delfino; Walker, Ezekiel; Zubov, Yurii; Heo, Hyeonu; Krokhin, Arkadii; Neogi, Arup
Abstract: A coupled resonant acoustic waveguide (CRAW) in a phononic crystal (PnC) was engineered to manipulate the propagation of ultrasonic waves within a conventional phononic bandgap for wavelength division multiplexing. The PnC device included two, forked, distinct CRAW waveguide channels that exhibited strong frequency and mode selectivity. Each branch was composed of cavities of differing volumes, with each giving rise to deep and shallow 'impurity' states. These states were utilized to select frequency windows where transmission along the channels was suppressed distinctly for each channel. Though completely a linear system, the mode sensitivity of each CRAW waveguide channel produced apparent nonlinear power dependence along each branch. Nonlinearity in the system arises from the combination of the mode sensitivity of each CRAW channel and small variations in the shape of the incident wavefront as a function of input power. The all-acoustic effect was then leveraged to realize an ultrasonic, spatial signal modulator, and logic element operating at 398 and 450 kHz using input power.